Outcome of Titanium Elastic Nailing System in Diaphyseal Femoral Fractures of Children in the Age Group of 4-12 years - Rahman, Mohammed Mahfoozur; Ahmed, Md Khaza; Sarwar, Md Golam; Hasan, Mehedi; Rahman, SM Tauhidur (Eastern Medical College Journal, 2024)
Background: Femoral shaft fractures are the most common major pediatric injuries treated by orthopedic surgeons. Management of femoral diaphyseal fracture in the age group of 4-12 years is controversial. The purpose of this study is to demonstrate the effectiveness of intramedullary fixation of femoral shaft fractures by using Titanium Elastic Nailing System (TENS). Methodology: Twenty-six (26) children in the range of 4-12 years with recent (<3 days) femoral shaft fracture (24 closed, 02 Grade-I compound) were stabilized with Titanium Elastic Nail (TEN), between January 2019 and June 2022 in Eastern Medical College Hospital, Cumilla and Cumilla Trauma Centre. The diameter of the individual nail was selected as per Flynn’s formula and the results were evaluated by Flynn’s criteria. All patients were followed radiologically as well as clinically until fractures healed and for any complications. Results: Among the twenty-six (26) cases 18 were boys and 8 were girls. Twenty-three (23) cases were managed by closed reduction while three (3) cases required open reduction. The time duration of surgery ranged 20-45 minutes. The hospital stay ranged between 5 to 8 days (mean 6.5 days). The mean duration of follow-up was 21 months (range: 3 - 39 months). All fractures were radiologically united at 8-12 weeks (mean 10 weeks) and full weight bearing was possible in a meantime of 9.5 weeks. According to Flynn’s criteria, excellent results were found in 24 (92.3%) cases and satisfactory in 2 (7.7%) cases. Limb lengthening was noticed in 6 cases and rotational mal alignment was seen in 1 case. Conclusion: Intramedullary fixation with Titanium Elastic Nail may be the preferred method for the treatment of femoral fractures in children aged 4-12 years. As it is a safe, minimally invasive, surgeon-friendly technique and shows very good functional and cosmetic results. Eastern Med Coll J. July 2023; 8 (2): 1-6